The Negative Impact of Free-Fire Online Game Addiction in Elementary School - Anwar Yoedo Pratama; zaka Hadikusuma (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Online game addiction is one attitude that will harm its users. The negative impact that will arise from playing online games can be seen from several aspects such as health, psychological, academic, social, and financial aspects. This research aims to describe the negative impacts that arise as a result of the excessive use of free-fire online games and to describe the efforts of teachers to overcome this addictive attitude. This research uses a case study approach and a type of qualitative research. The case study is research that is used to explore a particular phenomenon (case) at one time and collect in-depth information with various procedures. The method of data collection is done utilizing observation, interviews, and documentation. The validity of the data uses the triangulation technique and the research data analysis used is the Miles and Huberman interactive model. The research results show that on the ground playing free-fire online games without excessive control will cause several negative impacts including cause addiction, speaking rudely and dirty, neglecting real-world activities, and inability to socialize. Meanwhile, the efforts made by teachers to overcome addiction to free-fire online games are to provide advice and build good communication with parents.